Method for producing composite solid electrolyte
Patent Information
- Application Number
- JP2024544988
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-05-31
- Filing Date
- 2023-05-31
- Publication Date
- 2025-02-26
AI Technical Summary
【0014】 本発明による複合固体電解質の製造方法は、紫外線硬化性高分子である第1高分子及びセラミック化合物を含むセラミックイオン伝導体を形成することにより、リチウムイオンのイオン伝導を効果的に改善することができ、前記セラミックイオン伝導体を利用して複合固体電解質のイオン伝導度を向上させることができる。
Smart Images

Figure 2025505428000001_ABST
Abstract
Description
[Technical field]
[0001] This application claims the benefit of priority based on Korean Patent Application No. 10-2022-0066951 filed on May 31, 2022 and Korean Patent Application No. 10-2023-0070146 filed on May 31, 2023, and incorporates all contents disclosed in the documents of said Korean patent applications as part of this specification.
[0002] The present invention relates to a method for producing a composite solid electrolyte. [Background technology]
[0003] Lithium-ion batteries that use liquid electrolytes have a structure in which the negative and positive electrodes are separated by a separator, so if the separator is damaged due to deformation or external impact, a short circuit can occur, which can lead to risks such as overheating and explosion. Therefore, the development of a solid electrolyte that can ensure safety in the field of lithium-ion secondary batteries is a very important issue.
[0004] Lithium secondary batteries using solid electrolytes have the advantages of increased safety and the prevention of electrolyte leakage, which improves battery reliability and makes it easier to manufacture thin batteries. In addition, because lithium metal can be used as the negative electrode, the energy density can be improved, and it is expected to be used in small secondary batteries as well as large-capacity secondary batteries for electric vehicles, and is attracting attention as a next-generation battery.
[0005] Among solid electrolytes, polymer solid electrolytes may use polymer materials that are ion-conductive materials or inorganic materials such as oxides or sulfides that have ion-conductive properties. Composite solid electrolytes that are a mixture of polymer materials and inorganic materials have also been proposed.
[0006] Such conventional composite solid electrolytes are manufactured by preparing a solution or slurry in which a polymer and an inorganic material are mixed and dispersed, and then solution casting the solution onto a substrate and drying the solution at a high temperature. However, the conventional composite solid electrolyte manufacturing technology has a limitation in that the inorganic material is not uniformly dispersed in the polymer solution, resulting in non-uniform inorganic particle distribution in the composite solid electrolyte, making it difficult to manufacture a composite solid electrolyte with improved ionic conductivity.
[0007] In order to overcome these limitations of conventional composite solid electrolytes, there is a need to develop a technique for manufacturing a composite solid electrolyte in which a polymer and an inorganic material are uniformly dispersed to improve the ionic conductivity of the composite solid electrolyte including the same and which is capable of being processed continuously. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] Korean Patent Publication No. 10-2017-0045011 Summary of the Invention [Problem to be solved by the invention]
[0009] An object of the present invention is to provide a method for producing a composite solid electrolyte which has improved ionic conductivity and can be carried out in a continuous process.
[0010] Another object of the present invention is to provide an all-solid-state battery including the composite solid electrolyte produced by the above-mentioned production method. [Means for solving the problem]
[0011] In order to achieve the above object, the present invention provides a method for producing a first composite layer by mixing a first polymer, which is an ultraviolet curable polymer, a photopolymerization initiator, and a ceramic compound; (2) a second step of sintering the first composite layer to produce a ceramic ionic conductor; (3) a third step of coating the ceramic ion conductor layer with a composition including a second polymer and a lithium salt, and curing the composition to produce a second composite layer; The present invention provides a method for producing a composite solid electrolyte, in which the first to third steps are carried out continuously.
[0012] The present invention also provides a composite solid electrolyte produced by the production method of the present invention, comprising a ceramic ion conductor layer containing a ceramic compound, a second polymer, and a lithium salt.
[0013] The present invention also provides an all-solid-state battery including the composite solid electrolyte produced by the production method of the present invention. Effect of the Invention
[0014] The method for manufacturing a composite solid electrolyte according to the present invention can effectively improve ion conduction of lithium ions by forming a ceramic ion conductor including a first polymer, which is a UV-curable polymer, and a ceramic compound, and can improve the ion conductivity of the composite solid electrolyte by using the ceramic ion conductor.
[0015] Furthermore, the method for producing a composite solid electrolyte according to the present invention can produce the composite solid electrolyte in a continuous process, making mass production possible. [Brief description of the drawings]
[0016] [Figure 1] FIG. 1 is a flow chart of a method for producing a composite solid electrolyte of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] In the following, the present invention will be described in further detail to aid in understanding the invention.
[0018] The terms and words used in this specification and the claims should not be interpreted limited to their ordinary or dictionary meanings, but should be interpreted in a meaning and concept that is consistent with the technical idea of the present invention, based on the principle that an inventor can appropriately define the concept of a term in order to best describe his / her invention.
[0019] In the conventional method of manufacturing a composite solid electrolyte, a solution or slurry in which a polymer and an inorganic material are mixed and dispersed is coated on a substrate film by a method such as solution casting, and then dried. However, this method has a problem in that the ionic conductivity of the solid electrolyte is not improved due to the non-uniform dispersion of the inorganic material in the polymer solution.
[0020] In order to improve this, the present invention aims to provide a method for manufacturing a composite solid electrolyte having improved ion conductivity by uniformly dispersing particles of the ceramic compound in a ceramic ion conductor layer manufactured using a first polymer, which is a UV-curable polymer, and a ceramic compound.
[0021] In the method for producing the composite solid electrolyte, a solution containing a first polymer, which is a UV-curable polymer, and a ceramic compound is irradiated with ultraviolet light and then cured to produce a first composite, thereby uniformly dispersing the ceramic compound in the first polymer solution. By producing a ceramic ion conductor in which the ceramic compound particles are uniformly dispersed, the ionic conduction of lithium ions can be improved, and a composite solid electrolyte with improved ionic conductivity can be produced. In addition, the method for producing the composite solid electrolyte of the present invention can be produced in a continuous process, making mass production possible.
[0022] Method for producing composite solid electrolyte The present invention relates to a method for producing a composite solid electrolyte, and the method for producing a composite solid electrolyte of the present invention includes the steps of: (1) a first step of preparing a first composite layer by mixing a first polymer, which is an ultraviolet-curable polymer, a photopolymerization initiator, and a ceramic compound; (2) a second step of sintering the first composite layer to produce a ceramic ionic conductor layer; and (3) A third step of coating the ceramic ion conductor layer with a composition including a second polymer and a lithium salt and curing the composition to produce a second composite layer.
[0023] The first to third steps are carried out continuously.
[0024] Hereinafter, each step of the method for preparing the composite solid electrolyte according to the present invention will be described in detail.
[0025] The first step comprises: (1-1) preparing a composition for forming a first composite, the composition including a first polymer, which is a UV-curable polymer, a photopolymerization initiator, and a ceramic compound; (1-2) unwinding the base film using an unwinder and supplying it to a conveying path; (1-3) applying the composition for forming the first composite on the substrate film to form a coating film; (1-4) conveying the substrate film on which the coating film is formed to an ultraviolet ray irradiation section, irradiating the coating film with ultraviolet rays, and curing the coating film to produce a first composite layer; and (1-5) The method includes a step of winding and recovering the substrate film including the first composite layer using a rewinder.
[0026] The step (1-1) is a step of preparing a composition for forming a first composite, which includes a first polymer that is a UV-curable polymer, a photopolymerization initiator, and a ceramic compound.
[0027] The UV-curable polymer refers to a polymer that forms a cross-linked bond by using UV rays. When the UV-curable polymer is irradiated with UV rays in the presence of a photopolymerization initiator, a photopolymerization reaction is initiated to form a photocross-linked bond. Therefore, the UV-curable polymer has a property of exhibiting maximum absorbance in at least a part of a wavelength region or the entire region of the UV region (e.g., wavelengths of 300 nm to 400 nm) in an absorbance spectrum with respect to wavelength.
[0028] The first polymer may include at least one selected from the group consisting of polyisocyanurate (PIR), epoxy, polyurethane, polyacrylate, and poly(methyl methacrylate (PMMA)).
[0029] In the polyacrylate, examples of the UV-curable acrylate monomer include hexanediol diacrylate (HDDA), tripropylene glycol diacrylate (TPGDA), ethylene glycol diacrylate (EGDA), trimethylolpropane triacrylate (TMPTA), trimethylolpropane ethoxylated triacrylate (TMPEOTA), glycerol propoxylated triacrylate (GPTA), pentaerythritol tetraacrylate (PETA), and dipentaerythritol hexaacrylate (DPHA), but are not limited thereto. Any acrylate monomer commonly used in the field may be used without any particular limitation.
[0030] The photoinitiator refers to a material that initiates a photopolymerization reaction when exposed to ultraviolet light emitted from an ultraviolet irradiator.
[0031] Examples of the photopolymerization initiator include, but are not limited to, 1-hydroxy-cyclohexyl-phenyl ketone, 2-hydroxy-2-methyl-1-phenyl-1-propanone, 2-hydroxy-1-[4-(2-hydroxyethoxy)phenyl]2-methyl-1-propanone, methylbenzoyl formate, α,α-dimethoxy-α-phenylacetophenone, 2-benzoyl-2-(dimethylamino)-1-[4-(4-morpholinyl)phenyl]-1-butanone, 2-methyl-1-[4[(methylthio)phenyl]-2(4-morpholinyl)-1-propanediphenyl(2,4,6-trimethylbenzoyl)-phosphine oxide, or bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide. In addition, the photopolymerization initiator may be a commercially available product such as Irgacure 184, Irgacure 500, Irgacure 651, Irgacure 369, Irgacure 907, Darocur 1173, Darocur MBF, Irgacure 819, Darocur TPO, Irgacure 907, Esacure KIP 100F, etc. The photopolymerization initiator may be used alone or in combination of two or more different types.
[0032] The content of the photopolymerization initiator is 1 to 5 wt % based on the content of the first polymer. If the content of the photopolymerization initiator is less than 1 wt % or more than 5 wt % based on the content of the first polymer, cross-linking between the first polymer and the ceramic compound is not formed, and it may be difficult to form the first composite layer.
[0033] The ceramic compound is an oxide-based or phosphate-based solid electrolyte. The oxide-based or phosphate-based solid electrolyte is a garnet-type lithium-lanthanum-zirconium oxide (LLZO, Li7La3 Zr 2 O 12 ), perovskite-type lithium-lanthanum-titanium oxide (LLTO, Li 3x La 2 / 3-x TiO 3 ), phosphate-based NASICON-type lithium aluminum titanium phosphate (LATP, Li 1+x Al x Ti 2-x (PO 4 ) 3 ), lithium aluminum germanium phosphate (LAGP, Li 1.5 Al 0.5 Ge 1.5 (PO 4 ) 3 ) system, lithium-silicon-titanium phosphate system (LSTP, LiSiO 2 TiO 2 (PO 4 ) 3 ) and lithium-lanthanum-zirconium-titanium oxide (LLZTO) compounds. The oxide- or phosphate-based solid electrolytes have a very high grain boundary resistance, and therefore require a sintering process at 1000°C or higher. This causes problems such as lithium volatilization at high temperatures, phase transition, and impurity phase formation. However, oxide- or phosphate-based solid electrolytes generally have a maximum sintering temperature of 10 -4 ~10 -3 It has an ionic conductivity value of 1.0 S / cm, is stable in the high voltage range, and is stable in air, so it has the advantages of being easy to synthesize and handle.
[0034] Therefore, by preparing a hybrid solid electrolyte by mixing the first polymer and a different material according to the present invention, the shortcomings of each material can be compensated for.
[0035] The oxide-based or phosphate-based solid electrolyte has high high-temperature stability because it does not easily burn or ignite even under high-temperature conditions of 400° C. or more. Therefore, when the ceramic ion conductor layer includes the oxide-based or phosphate-based solid electrolyte, it is possible to improve the high-temperature stability and ionic conductivity as well as the mechanical strength of the composite solid electrolyte for a lithium secondary battery.
[0036] The first composite-forming composition is prepared by adding a photopolymerization initiator and a ceramic compound to a first polymer solution, which is a UV-curable polymer.
[0037] The solvent used in the preparation of the first polymer solution is a polar solvent, such as water, that is, the first polymer solution is an aqueous solution.
[0038] The concentration of the first polymer solution can be appropriately adjusted in consideration of the extent to which the coating process can proceed smoothly when the first complex-forming solution is applied to the base film. For example, the first polymer is contained in an amount of 5 to 20 wt % relative to the total weight of the first polymer aqueous solution, specifically, 5 wt % or more, 7 wt % or more, or 9 wt % or more, and 13 wt % or less, 17 wt % or less, or 20 wt % or less. If the first polymer is contained in an amount of less than 5 wt %, the concentration is too low and may run off when applied to the base film, and if it is contained in an amount of more than 20 wt %, it may be difficult to apply the first polymer in a uniform thin film.
[0039] The ceramic compound is contained in an amount of 1 part by weight or more and less than 10 parts by weight per part by weight of the first polymer. More specifically, the weight ratio of the first polymer and the ceramic compound is 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, or 1:9. When the ceramic compound is contained in an amount of less than 1 part by weight per part by weight of the first polymer, the connection between the ceramic compounds is not smooth after the sintering process, which is the second process, and the ceramic ion conductor having a cross-linked structure is difficult to form, and the mechanical properties are weak, so that the ceramic compound is easily broken or destroyed, and thus a composite solid electrolyte cannot be manufactured. When the ceramic compound is contained in an amount of more than 10 parts by weight per part by weight of the first polymer, the ceramic compound is not uniformly dispersed in the first polymer, and the ceramic compound particles aggregate with each other, and phase separation occurs between the first polymer and the aggregated ceramic compound particles, making it difficult to form a ceramic ion conductor layer, resulting in a composite solid electrolyte having reduced ion conductivity.
[0040] The step (1-2) is a step of unwinding the base film using an unwinder and supplying it to a transport path.
[0041] The unwinder winds up and supplies the base film wound in a roll shape to a predetermined transport path, and can unwind and supply the base film by its own drive, or can unwind and supply the base film by the drive force of a rewinder that winds up the base film including the first composite.
[0042] Therefore, the first process of the present invention is a roll-to-roll process.
[0043] The substrate film is not particularly limited as long as it can play a role as a support on which the first composite-forming composition is applied. For example, the substrate film is SS (stainless steel), polyethylene terephthalate film, polytetrafluoroethylene film, polyethylene film, polypropylene film, polybutene film, polybutadiene film, vinyl chloride copolymer film, polyurethane film, ethylene-vinyl acetate film, ethylene-propylene copolymer film, ethylene-ethyl acrylate copolymer film, ethylene-methyl acrylate copolymer film, or polyimide film.
[0044] The step (1-3) is a step of coating the first composite-forming composition on the substrate film to form a coating film.
[0045] The coating method in the present invention is not particularly limited as long as it can coat the composition for forming the first complex on the substrate film in the form of a film, for example, bar coating, roll coating, spin coating, slit coating, die coating, blade coating, comma coating, slot die coating, lip coating, spray coating, or solution casting.
[0046] In one embodiment of the present invention, a solution casting method can be used. More specifically, the first composite-forming composition prepared in step (1-1) is placed in a mixer, and the mixer is placed above a substrate film, and the first composite-forming composition is continuously cast onto the substrate film fed to a transport path to form a coating film.
[0047] The step (1-4) is a step of transporting the substrate film having the coating film formed thereon to an ultraviolet ray irradiation section, irradiating the coating film with ultraviolet rays, and curing the coating film to produce a first composite layer.
[0048] The wavelength of the ultraviolet (UV) light used in the curing reaction is 200 to 400 nm.
[0049] The UV curing is fast, so the first composite layer can be produced quickly.
[0050] After the step (1-4), the method may further include a step of transporting the substrate film including the first composite layer to a thermal aging section to thermally age the substrate film including the first composite layer.
[0051] The heat aging may be performed at 50°C to 100°C, specifically, 50°C or more, 60°C or more, or 70°C or more, and 80°C or less, 90°C or less, or 100°C or less.
[0052] The first composite layer may be further cured through the thermal aging, and the amount of unreacted functional groups in the first polymer may be reduced, thereby improving the mechanical properties of the first composite layer. In addition, the residual stress formed in the first polymer during the coating and UV curing process may be relieved. In addition, the adhesive strength between the substrate film and the first composite layer may be improved, thereby solving the problem of the first composite layer peeling off from the substrate during processing.
[0053] The step (1-5) is a step of winding and recovering the substrate film including the first composite layer using a rewinder.
[0054] The rewinder can wind up the base film including the first composite layer into a roll and recover it, and can wind up the base film including the first composite layer by its own drive.
[0055] In the method for producing the composite solid electrolyte of the present invention, the first step is a roll-to-roll process, which allows for continuous production.
[0056] The second step may be carried out continuously after the step (1-5). The second step includes: (2-1) unwinding the base film including the first composite layer using an unwinder, peeling the first composite layer from the base film, and slitting the first composite layer; and (2-2) Sintering the slit first composite layer to produce a ceramic ion conductor layer.
[0057] The step (2-1) is a step of unwinding the base film including the first composite layer using an unwinder, peeling the first composite layer from the base film, and slitting the first composite layer.
[0058] The unwinder winds up and supplies the base film including the first composite layer wound in a roll to a predetermined transport path, and can wind up and supply the base film including the first composite layer by its own drive.
[0059] Thereafter, the first composite layer is peeled off from the base film, and then slit into a desired area.
[0060] The step (2-2) is a step of sintering the substrate film including the slit first composite layer to manufacture a ceramic ion conductor layer.
[0061] As used herein, sintering refers to the process of subjecting the first composite layer to sufficient temperature and pressure to reduce it to a harder mass of particles.
[0062] The ceramic ion conductor layer may be prepared by sintering the first composite layer to pyrolyze the first polymer component and sinter the remaining ceramic compound particles.
[0063] Through the sintering process, the first polymer serves as a support for connecting the ceramic compound particles to each other, and the ceramic compound particles are connected to each other to form a ceramic ion conductor having a cross-linked structure.
[0064] The ceramic ion conductor layer comprises a cross-linked structure that includes a ceramic compound.
[0065] The ceramic ion conductor may serve to form an ion conduction path for lithium ions.
[0066] The sintering can be performed by appropriately selecting conditions that allow the first polymer component to be pyrolyzed and the ceramic compound particles to be linked to each other to form an ion conductor with a cross-linked structure. For example, the sintering can be performed at a temperature of 800°C to 1300°C, and more specifically, the sintering temperature is 850°C or more, 900°C or more, 950°C or more, and 1300°C or less, 1250°C or less, 1200°C or less.
[0067] The third step may be carried out consecutively after the step (2-2). The third step includes: (3-1) preparing a composition comprising a second polymer and a lithium salt; (3-2) coating the ceramic ion conductor layer with the composition; and (3-3) curing the ceramic ion conductor layer coated with the composition to produce a second composite layer.
[0068] The second composite layer includes the ceramic ion conductor layer, so that a composite solid electrolyte having improved ion conductivity can be produced.
[0069] The step (3-1) is a step of preparing a composition including a second polymer and a lithium salt.
[0070] The second polymer has excellent solubility for lithium salts, and the polymer solution easily permeates the ceramic ion conductor, facilitating the final production of a composite solid electrolyte. Specific examples of the second polymer include one or more selected from the group consisting of polyvinyl alcohol (PVA), polyethylene oxide (PEO), polyacrylate, poly(methyl methacrylate (PMMA), PSTFSI, polyurethane, nylon, poly(dimethylsiloxane), gelatin, methylcellulose, agar, dextrin, poly(vinyl pyrrolidone), poly(acrylic amide), poly(acrylic acid), starch-carboxymethylcellulose, hyaluronic acid-methylcellulose, chitosan, poly(N-isopropylacrylamide), and amino-terminated PEG.
[0071] In the present invention, the lithium salt is contained in a dissociated state within the structure formed by the ceramic ion conductor layer, thereby improving the ionic conductivity of the composite solid electrolyte, and the lithium salt is mainly dissociated within the second polymer, thereby compensating for the loss of lithium ions generated from the ceramic compound particles during the high-temperature sintering process in the second step.
[0072] The lithium salt is LiNO 3 , LiOH, LiCl, LiBr, LiI, LiClO 4 , LiBF 4 , LiB 10 Cl 10 , LiPF6 , LiCF 3 SO 3 , LiCF 3 CO 2 , LiAsF 6 , LiSbF 6 , LiAlCl 4 , C.H. 3 SO 3 Li, C.F. 3 SO 3 Li, LiSCN, LiC(CF 3 SO 2 ) 3 , (CF 3 SO 2 ) 2 NLi and (FSO 2 ) 2 NLi.
[0073] The composition is prepared by adding a lithium salt to a solution containing a second polymer.
[0074] The solvent used in preparing the second polymer solution is a polar solvent, such as water, that is, the second polymer solution is an aqueous polymer solution.
[0075] The concentration of the solution containing the second polymer can be appropriately adjusted in consideration of the smooth progress of the coating process for coating the ceramic ion conductor layer. For example, the second polymer is contained in an amount of 5 to 20 wt %, specifically, 5 wt % or more, 7 wt % or more, or 9 wt % or more, and 13 wt % or less, 17 wt % or less, or 20 wt % or less, based on the total weight of the second polymer solution. If the second polymer is contained in an amount of less than 5 wt %, the concentration is too dilute and the surface of the ceramic ion conductor layer cannot be coated, and if the second polymer is contained in an amount of more than 20 wt %, the concentration is too high and it is difficult to uniformly coat the surface of the ceramic ion conductor layer.
[0076] The molar ratio ([Li] / [G]) of the molar concentration ([G]) of the second polymer to the lithium ([Li]) of the lithium salt is 0.1 to 0.5, specifically, 0.1 or more, 0.2 or more, or 0.3 or more, and 0.4 or less, or 0.5 or less. If the molar ratio ([Li] / [G]) is less than 0.1, the content of the lithium salt may decrease, and the ionic conductivity of the composite solid electrolyte may decrease, whereas if the molar ratio ([Li] / [G]) is more than 0.5, the ionic conductivity may decrease due to the aggregation of lithium ions. Therefore, the composite solid electrolyte according to the present invention requires a composition of the second polymer and an appropriate amount of lithium salt in the second composite layer.
[0077] The step (3-2) is a step of coating the ceramic ion conductor layer with the composition.
[0078] The coating method is not particularly limited as long as it is a method commonly used in the art, and dipping, spraying, doctor blade, spin coating, etc. can be used, and dipping is preferably used.
[0079] The step (3-3) is a step of curing the ceramic ion conductor layer coated with the composition to form a second composite layer.
[0080] The curing is either thermal or UV curing.
[0081] The ultraviolet curing is the same as described above.
[0082] The thermal curing is carried out while the ceramic ion conductor layer is immersed in the mixed solution.
[0083] The thermal curing step is performed at, but is not limited to, 50° C. to 150° C. For example, the thermal curing step is performed at, but is not limited to, 50° C. to 150° C., 60° C. to 150° C., 70° C. to 150° C., 80° C. to 150° C., 90° C. to 150° C., 100° C. to 150° C., 50° C. to 140° C., 50° C. to 130° C., 50° C. to 120° C., 50° C. to 110° C., or 50° C. to 100° C. If the thermal curing step is performed below this temperature range, the formation of the second composite may be incomplete, and if the thermal curing step is performed above this temperature range, the preparation of the composite solid electrolyte may be difficult due to thermal decomposition of the second polymer and the lithium salt.
[0084] The ceramic ion conductor layer coated with the second composite layer is the composite solid electrolyte to be prepared in the present invention, and the composite solid electrolyte has improved ion conductivity, specifically, 10 -5 Although the composite solid electrolyte is a solid electrolyte, it exhibits ion conductivity at a level equal to or higher than that of conventional liquid electrolytes, and can improve the performance of all-solid-state batteries.
[0085] The method for producing the composite solid electrolyte of the present invention is a continuous process that is carried out continuously, and thus allows for mass production.
[0086] The method for producing the composite solid electrolyte of the present invention is a continuous process in which the first to third steps are carried out continuously, and thus mass production is possible.
[0087] Composite solid electrolyte The present invention also relates to a composite solid electrolyte comprising a ceramic ion conductor layer containing a ceramic compound, a second polymer, and a lithium salt, the composite solid electrolyte being produced by the above-mentioned production method of the present invention.
[0088] The second polymer and the lithium salt in the ceramic ion conductor layer are the same as those described above.
[0089] The ceramic ion conductor layer is obtained by sintering the first composite layer. Thus, the ceramic ion conductor layer includes a cross-linked structure formed by connecting the ceramic compound particles to each other. The first polymer serves as a support for connecting the ceramic compound particles to each other.
[0090] Conventional composite solid electrolytes are manufactured by coating or dispersing a solution or slurry of a mixture of polymer and inorganic material on a substrate using a method such as solution casting, and then drying it. However, this method has a problem in that the ionic conductivity of the solid electrolyte is not improved due to non-uniform dispersion and precipitation of the inorganic material in the polymer solution.
[0091] To improve this, the present invention provides a composite solid electrolyte comprising a ceramic ion conductor layer having a cross-linked structure forming an ion conduction path for lithium ions, a second polymer, and a lithium salt. The ceramic ion conductor has ceramic compound particles uniformly dispersed therein, thereby improving the ion conductivity of the composite solid electrolyte.
[0092] The composite solid electrolyte is in the form of a free standing film. The free standing film means a film that can maintain a film shape by itself without a separate support at room temperature and pressure.
[0093] The free-standing film exhibits elasticity and minimizes brittleness, and has the properties of a support that stably contains lithium ions, making it an appropriate form for a composite solid electrolyte.
[0094] In the present invention, the ionic conductivity of the composite solid electrolyte is 10 -5 S / cm or more.
[0095] Although the composite solid electrolyte is a solid electrolyte, it exhibits ionic conductivity at a level equal to or higher than that of conventional liquid electrolytes, and can improve the performance of all-solid-state batteries.
[0096] All solid state battery The present invention also relates to an all-solid-state battery including the composite solid electrolyte, the all-solid-state battery including a negative electrode, a positive electrode, and a composite solid electrolyte interposed between the negative electrode and the positive electrode, the composite solid electrolyte being produced by the production method and having the characteristics described above.
[0097] Specifically, the composite solid electrolyte contains a ceramic ion conductor and improves the ion conduction of lithium ions, making it suitable as an electrolyte for an all-solid-state battery.
[0098] In the present invention, the positive electrode included in the all-solid-state battery may include a positive electrode active material layer, and the positive electrode active material layer may be formed on one surface of a positive electrode current collector.
[0099] The positive electrode active material layer includes a positive electrode active material, a binder, and a conductive material.
[0100] The positive electrode active material is not particularly limited as long as it is a material capable of reversibly absorbing and releasing lithium ions. For example, lithium cobalt oxide (LiCoO 2 ), lithium nickel oxide (LiNiO 2 ), Li[Ni x Co y Mn z M v ]O 2 (wherein M is any one or more elements selected from the group consisting of Al, Ga, and In, and 0.3≦x<1.0, 0≦y, ≦0.5, 0≦v≦0.1, and x+y+z+v=1), Li (Li a M b-a-b’ M' b’ )O 2-c A c(wherein 0≦a≦0.2, 0.6≦b≦1, 0≦b'≦0.2, 0≦c≦0.2, M includes n and at least one selected from the group consisting of Ni, Co, Fe, Cr, V, Cu, Zn, and Ti, M' is at least one selected from the group consisting of Al, Mg, and B, and A is at least one selected from the group consisting of P, F, S, and N), or a compound substituted with one or more transition metals, such as a compound of the formula Li 1+y Mn 2-y O 4 (where y is 0 - 0.33), LiMnO 3 , LiMn 2 O 3 , LiMnO 2 Lithium manganese oxide, lithium copper oxide (Li 2 CuO 2 ), LiV 3 O 8 , Life 3 O 4 , V 2 O 5 , Cu 2 V 2 O 7 Vanadium oxides such as LiNi 1-y MyO 2 (where M=Co, Mn, Al, Cu, Fe, Fe, Mg, B or Ga, and y=0.01 - 0.3), 2 Mn 3 MO 8 (where M=Co, Ni, Fe, Cr, Zn, or Ta, y=0.01 - 0.1) or Li 2 Mn 3 MO 8 Lithium manganese oxides represented by the formula LiMn (where M=Fe, Co, Ni, Cu, or Zn) are used. 2 O 4、 Disulfide compounds, Fe 2 (MoO 4 ) 3 These include, but are not limited to:
[0101] The positive electrode active material is contained in an amount of 40 to 80 wt % based on the total weight of the positive electrode active material layer. Specifically, the content of the positive electrode active material is 40 wt % or more or 50 wt % or more and 70 wt % or less or 80 wt % or less. If the content of the positive electrode active material is less than 40 wt %, the connectivity between the wet positive electrode active material layer and the dry positive electrode active material layer may be insufficient, and if it exceeds 80 wt %, the mass transfer resistance may be large.
[0102] The binder may be a component that assists in binding the positive electrode active material to the conductive material and the like and binding to the current collector, and may be, for example, styrene-butadiene rubber, acrylated styrene-butadiene rubber, acrylonitrile copolymer, acrylonitrile-butadiene rubber, nitrile butadiene rubber, acrylonitrile-styrene-butadiene copolymer, acrylic rubber, butyl rubber, fluororubber, polytetrafluoroethylene, polyethylene, polypropylene, ethylene / propylene copolymer, polybutadiene, polyethylene oxide, chlorosulfonated polyethylene, polyvinylpyrrolidone, polyvinylpyridine, polyvinyl alcohol, polyvinyl acetate, polyvinyl chloride, polyphosphazene, polyacrylonitrile, polyvinyl chloride ... The binder may include at least one selected from the group consisting of styrene-butadiene rubber, polytetrafluoroethylene, carboxymethylcellulose, polystyrene, latex, acrylic resin, phenolic resin, epoxy resin, carboxymethylcellulose, hydroxypropylcellulose, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethylcellulose, cyanoethylsucrose, polyester, polyamide, polyether, polyimide, polycarboxylate, polycarboxylic acid, polyacrylic acid, polyacrylate, lithium polyacrylate, polymethacrylic acid, polymethacrylate, polyacrylamide, polyurethane, polyvinylidene fluoride, and poly(vinylidene fluoride)-hexafluoropropene. Preferably, the binder includes at least one selected from the group consisting of styrene-butadiene rubber, polytetrafluoroethylene, carboxymethylcellulose, polyacrylic acid, lithium polyacrylate, and polyvinylidene fluoride.
[0103] The binder may be contained in an amount of 1 to 30% by weight based on the total weight of the positive electrode active material layer, and specifically, the binder content is 1% by weight or more or 3% by weight or more and 15% by weight or less or 30% by weight or less. If the binder content is less than 1% by weight, the adhesive strength between the positive electrode active material and the positive electrode current collector may decrease, and if it exceeds 30% by weight, the adhesive strength is improved, but the content of the positive electrode active material may decrease accordingly, and the battery capacity may decrease.
[0104] The conductive material is not particularly limited as long as it prevents side reactions in the internal environment of the all-solid-state battery, does not cause chemical changes in the battery, and has excellent electrical conductivity. Representative examples include graphite or conductive carbon. Examples of the conductive material include graphite such as natural graphite and artificial graphite, carbon black, acetylene black, ketjen black, denka black, thermal black, channel black, furnace black, lamp black, summer black, and other carbon blacks, carbon-based substances having a graphene or graphite crystal structure, conductive fibers such as carbon fibers and metal fibers, metal powders such as carbon fluoride, aluminum powder, and nickel powder, conductive whiskey such as zinc oxide and potassium titanate, conductive oxides such as titanium oxide, and conductive polymers such as polyphenylene derivatives can be used alone or in a mixture of two or more kinds, but are not limited to these.
[0105] The conductive material is usually included in an amount of 0.5 wt % to 30 wt % based on the total weight of the positive electrode active material layer, and specifically, the content of the conductive material is 0.5 wt % or more or 1 wt % or more and 20 wt % or less or 30 wt % or less. If the content of the conductive material is too small, such as less than 0.5 wt %, it is difficult to expect an improvement in electrical conductivity or the electrochemical properties of the battery may be deteriorated, and if the content is too large, such as more than 30 wt %, the amount of the positive electrode active material may be relatively small, and the capacity and energy density may be reduced. The method of incorporating the conductive material into the positive electrode is not significantly limited, and a conventional method known in the art, such as coating on the positive electrode active material, may be used.
[0106] In addition, the positive electrode current collector supports the positive electrode active material layer and transfers electrons between an external conductive wire and the positive electrode active material layer.
[0107] The positive electrode current collector is not particularly limited as long as it does not cause a chemical change in the all-solid-state battery and has high electronic conductivity. For example, the positive electrode current collector can be made of copper, stainless steel, aluminum, nickel, titanium, palladium, baked carbon, copper or stainless steel surface-treated with carbon, nickel, silver, or the like, or an aluminum-cadmium alloy.
[0108] The positive electrode current collector may have a fine uneven structure on the surface thereof or a three-dimensional porous structure in order to strengthen the bonding force with the positive electrode active material layer, and thus the positive electrode current collector may have various forms such as a film, sheet, foil, mesh, net, porous body, foam, nonwoven fabric, etc.
[0109] The positive electrode may be prepared according to a conventional method, specifically, by mixing a positive electrode active material, a conductive material, and a binder in an organic solvent to prepare a composition for forming a positive electrode active material layer, applying the composition onto a positive electrode current collector, drying the composition, and optionally compressing the composition into a current collector to improve the electrode density. At this time, it is preferable to use an organic solvent that can uniformly disperse the positive electrode active material, the binder, and the conductive material and that can be easily evaporated. Specific examples of the organic solvent include acetonitrile, methanol, ethanol, tetrahydrofuran, water, and isopropyl alcohol.
[0110] In the present invention, the negative electrode included in the all-solid-state battery includes a negative electrode active material layer, and the negative electrode active material layer is formed on one surface of a negative electrode current collector.
[0111] The negative electrode active material is a lithium ion (Li +The intercalation or deintercalation of lithium ions is not particularly limited, and may be carried out by any suitable method.
[0112] The lithium ion (Li + The material capable of reversibly inserting or de-inserting the lithium ion (Li + The material capable of reacting with lithium (Li) to reversibly form a lithium-containing compound is, for example, tin oxide, titanate, or silicon. The lithium alloy is, for example, an alloy of lithium (Li) and a metal selected from the group consisting of sodium (Na), potassium (K), rubidium (Rb), cesium (Cs), francium (Fr), beryllium (Be), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), radium (Ra), aluminum (Al), and tin (Sn).
[0113] Preferably, the negative electrode active material is lithium metal, specifically in the form of a lithium metal thin film or lithium metal powder.
[0114] The negative active material is included in an amount of 40 to 80 wt % based on the total weight of the negative active material layer. Specifically, the content of the negative active material is 40 wt % or more or 50 wt % or more and 70 wt % or less or 80 wt % or less. If the content of the negative active material is less than 40 wt %, the connectivity between the wet negative active material layer and the dry negative active material layer may be insufficient, and if it exceeds 80 wt %, the mass transfer resistance may be large.
[0115] The binder is as described above in relation to the positive electrode active material layer.
[0116] The conductive material is the same as that described above in the positive electrode active material layer.
[0117] The negative electrode current collector is not particularly limited as long as it does not cause a chemical change in the battery and has conductivity, and examples of the negative electrode current collector that can be used include copper, stainless steel, aluminum, nickel, titanium, baked carbon, copper or stainless steel surface-treated with carbon, nickel, titanium, silver, aluminum-cadmium alloy, etc. Similarly to the positive electrode current collector, the negative electrode current collector can be in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc., with fine irregularities formed on the surface.
[0118] The method for manufacturing the negative electrode is not particularly limited, and the negative electrode may be manufactured by forming a negative electrode active material layer on a negative electrode current collector using a method for forming a layer or film commonly used in the art. For example, methods such as compression bonding, coating, deposition, etc. may be used. In addition, the negative electrode of the present invention also includes a case where a thin metallic lithium film is formed on a metal plate by initial charging after assembling a battery without a thin lithium film on the negative electrode current collector.
[0119] The present invention also provides a battery module including the all-solid-state battery as a unit cell, a battery pack including the battery module, and a device including the battery pack as a power source.
[0120] In this case, specific examples of the device include, but are not limited to, power tools powered by an electric motor, electric vehicles including electric vehicles (EV), hybrid electric vehicles (HEV), plug-in hybrid electric vehicles (PHEV), etc., electric bicycles (E-bikes), electric two-wheeled vehicles including electric scooters (E-scooters), electric golf carts, and power storage systems.
[0121] MODE FOR CARRYING OUT THEINVENTION Below, preferred examples are shown to aid in understanding the present invention. The following examples are merely illustrative of the present invention, and it will be apparent to those skilled in the art that various changes and modifications are possible within the scope of the category and technical spirit of the present invention. Naturally, these changes and modifications also fall within the scope of the appended claims.
[0122] In the examples and comparative examples described later, a ceramic ion conductor containing a first polymer and a ceramic compound as shown in Table 1 below was produced, and a composite solid electrolyte containing the ceramic ion conductor was produced.
[0123] [Table 1]
[0124] Working Example Example 1 Preparation of composite solid electrolyte (1) Composite production Thiol-ene polyisocyanurate (PIR) was mixed with distilled water (DI water) to prepare a 10 wt% PIR aqueous solution. A solution containing LLZO powder, a ceramic compound, was prepared in the PIR aqueous solution. 1 wt% of 2-hydroxy-2-methyl-1-phenyl-1-propanone was added as a photopolymerization initiator to the solution. The weight ratio of PIR to LLZO was 1:2.
[0125] The solution was put into a mixer and then coated by a bar coating method on a base film (SS foil) fed to a conveying path by an unwinder, which was then conveyed to an ultraviolet irradiation section where it was irradiated with ultraviolet (UV) light and cured to induce crosslinking of the PIR, thereby producing a first composite layer having a crosslinked structure. The base film including the first composite layer thus produced was wound and collected using a rewinder.
[0126] (2) Fabrication of the ceramic ion conductor layer The first composite layer was peeled off from the substrate film including the first composite layer, which was fed to a transport path by an unwinder, and the peeled first composite layer was slit into a desired size. The slit first composite layer was heated from room temperature to 800° C. at a rate of 1° C. / min and sintered at 800° C. for 2 hours to thermally decompose the PIR component contained in the first composite layer and sinter the remaining LLZO particles to produce a ceramic ion conductor layer.
[0127] (3) Manufacturing of composite solid electrolyte A solution containing PVA and LiTFSI was prepared (wherein the molar ratio ([Li] / [O]) of "O" contained in the PVA and "Li" contained in the lithium salt was 0.4). The ceramic ion conductor layer was immersed in the prepared solution for 5 minutes and then dried in a vacuum drying oven at 100°C for 12 hours to prepare a composite solid electrolyte.
[0128] Example 2 A composite solid electrolyte was prepared in the same manner as in Example 1, except that LSTP was used instead of the ceramic compound LLZO.
[0129] Example 3 A composite solid electrolyte was prepared in the same manner as in Example 1, except that the weight ratio of the UV-curable polymer (PIR) and the ceramic compound (LLZO) was 1:10.
[0130] Example 4 A composite solid electrolyte was prepared in the same manner as in Example 1, except that the weight ratio of the UV-curable polymer (PIR) and the ceramic compound (LLZO) was 10:1.
[0131] Example 5 A composite solid electrolyte was prepared in the same manner as in Example 1, except that the content of the photopolymerization initiator was 0.1 wt %.
[0132] Example 6 A composite solid electrolyte was prepared in the same manner as in Example 1, except that the content of the photopolymerization initiator was 0.4 wt %.
[0133] Example 7 A composite solid electrolyte was produced in the same manner as in Example 1, except that the molar ratio ([Li] / [O]) of “O” contained in the PVA and “Li” contained in the lithium salt was 0.08.
[0134] Example 8 A composite solid electrolyte was produced in the same manner as in Example 1, except that the molar ratio ([Li] / [O]) of “O” contained in the PVA to “Li” contained in the lithium salt was 0.52.
[0135] Example 9 A composite solid electrolyte was prepared in the same manner as in Example 1, except that PEO was used instead of the polymeric PVA.
[0136] Example 10 A composite solid electrolyte was prepared in the same manner as in Example 1, except that PIR was used instead of the polymeric PVA.
[0137] Comparative Example 1 A composite solid electrolyte was prepared in the same manner as in Example 1, except that the steps after the sintering process were not carried out after the preparation of the composite.
[0138] Comparative Example 2 A composite solid electrolyte was prepared in the same manner as in Comparative Example 1, except that the curing was performed after irradiation with ultraviolet (UV) rays, and the curing was performed by drying at 80° C. for 2 hours.
[0139] Experimental Example 1 In order to measure the ionic conductivity of the film-shaped composite solid electrolytes prepared in the examples and comparative examples, 2 The composite solid electrolyte was punched out into a circular shape of a desired size, and the punched composite solid electrolyte was placed between two pieces of stainless steel (SS) to prepare a coin cell.
[0140] The resistance was measured using an electrochemical impedance spectrometer (EIS, VM3, Bio Logic Science Instrument) at 25° C. under conditions of an amplitude of 10 mV and a scan range of 500 KHz to 20 MHz, and the ionic conductivity of the composite solid electrolyte was calculated using Equation 1 below.
[0141]
number
[0142] In the above formula 1, σi is the ionic conductivity (S / cm) of the composite solid electrolyte, R is the resistance (Ω) of the composite solid electrolyte measured by the electrochemical impedance spectrometer, L is the thickness (μm) of the composite solid electrolyte, and A is the area (cm 2 )
[0143] The ionic conductivity of the composite solid electrolyte calculated using Equation 1, the possibility of forming a freestanding film, and the observation results of the appearance of the composite solid electrolyte are shown in Table 2. Here, the possibility of forming a freestanding film (formed: ◯, not formed: X) and the appearance of the composite solid electrolyte were observed with the naked eye.
[0144] [Table 2]
[0145] As shown in Table 2, a solution in which the first polymer, which is the UV-curable polymer, and the ceramic compound are mixed in an appropriate weight ratio range is irradiated with UV light and cured, and then a sintering process is performed to form a ceramic ion conductor. It was confirmed that a composite solid electrolyte can be manufactured using the ceramic ion conductor manufactured through the above process (Examples 1, 2, 9, and 10).
[0146] In Examples 3 and 4, it was confirmed that a ceramic ion conductor was not formed when the weight ratio of the first polymer, which is a UV curable polymer, to the ceramic compound was more than 1:10 or less than 10:1. Therefore, it was confirmed that in order to form a ceramic ion conductor layer according to the present invention, a proper range of the weight ratio of the first polymer to the ceramic compound must be satisfied.
[0147] In Examples 5 and 6, it was confirmed that a crosslinked film could not be produced unless the content of the photopolymerization initiator was within the appropriate range.
[0148] In Examples 7 and 8, when preparing the composite solid electrolyte, if the concentrations of the second polymer and the lithium salt are outside the range of 0.1 to 0.5, it was confirmed that a film cannot be formed, which is unsuitable for preparing the desired composite solid electrolyte.
[0149] From Comparative Examples 1 and 2, it was found that even if a UV-curable polymer is simply used, a ceramic ion conductor or a crosslinked film cannot be formed unless UV irradiation and curing are performed or a sintering process is applied.
[0150] Although the present invention has been described above with reference to limited embodiments and drawings, the present invention is not limited thereto, and it is of course possible for a person having ordinary knowledge in the technical field to which the present invention pertains to make various modifications and variations within the technical spirit of the present invention and the equivalent scope of the claims described below.
Claims
1. (1) a first step of preparing a first composite layer by mixing a first polymer, which is an ultraviolet-curable polymer, a photopolymerization initiator, and a ceramic compound; (2) a second step of sintering the first composite layer to produce a ceramic ion conductor layer; and (3) a third step of coating the ceramic ion conductor layer with a composition including a second polymer and a lithium salt and curing the composition to produce a second composite layer; The method for producing a composite solid electrolyte, wherein the first to third steps are carried out consecutively.
2. 2. The method of claim 1, wherein the first polymer comprises at least one selected from the group consisting of polyisocyanurate (PIR), epoxy, polyurethane, polyacrylate, and polymethyl methacrylate (PMMA).
3. 2. The method for producing a composite solid electrolyte according to claim 1, wherein the ceramic compound comprises at least one selected from the group consisting of lithium-lanthanum-zirconium oxide (LLZO), lithium-silicon-titanium phosphate (LSTP), lithium-lanthanum-titanium oxide (LLTO), lithium-aluminum-titanium phosphate (LATP), lithium-aluminum-germanium phosphate (LAGP) and lithium-lanthanum-zirconium-titanium oxide (LLZTO) compounds.
4. The method for producing a composite solid electrolyte according to claim 1 , wherein the ceramic compound is contained in an amount of 1 part by weight or more and less than 10 parts by weight per 1 part by weight of the first polymer.
5. The method of claim 1 , wherein the photopolymerization initiator is contained in an amount of 1 to 5 wt % based on the content of the first polymer.
6. The method for producing a composite solid electrolyte according to claim 1 , wherein the ceramic ion conductor layer includes a cross-linked structure between the first polymer and a ceramic compound.
7. The second polymer may be selected from the group consisting of polyvinyl alcohol (PVA), polyethylene oxide (PEO), polyacrylate, poly(methyl methacrylate, PMMA), poly(4-styrenesulfonyl(trifluoromethylsulfonyl)imide (PSTFSI), polyurethane, nylon, poly(dimethylsiloxane), gelatin, methylcellulose, agar, dextrin, poly(vinyl pyrrolidone), poly(acrylamide), and the like.
2. The method for producing the composite solid electrolyte according to claim 1, comprising at least one selected from the group consisting of poly(acrylic acid), starch-carboxymethylcellulose, hyaluronic acid-methylcellulose, chitosan, poly(N-isopropylacrylamide), and amino-terminated polyethylene glycol.
8. The lithium salt is LiNO 3 , LiOH, LiCl, LiBr, LiI, LiClO 4 , LiBF 4 , LiB 10 C 10 , LiPF 6 , LiCF 3 SO 3 , LiCF 3 CO 2 , LiAsF 6 , LiSbF 6 , LiAlCl 4 , C.H. 3 SO 3 Li, C.F. 3 SO 3 Li, LiSCN, LiC(CF 3 SO 2 ) 3 , (CF 3 SO 2 ) 2 NLi and (FSO 2 ) 2 The method for producing a composite solid electrolyte according to claim 1, wherein the composite solid electrolyte contains one or more selected from the group consisting of NLi.
9. The first step comprises: (1-1) preparing a composition for forming a first composite, the composition including a first polymer, which is a UV-curable polymer, a photopolymerization initiator, and a ceramic compound; (1-2) unwinding the base film using an unwinder and supplying it to a conveying path; (1-3) applying the composition for forming the first composite on the substrate film to form a coating film; (1-4) conveying the substrate film on which the coating film is formed to an ultraviolet ray irradiation section, irradiating the coating film with ultraviolet rays, and curing the coating film to produce a first composite layer; and (1-5) A method for producing a composite solid electrolyte, comprising the step of winding and recovering the substrate film including the first composite layer using a rewinder.
10. The method for producing a composite solid electrolyte according to any one of claims 1 to 8, further comprising, after the step (1-4), a step of conveying the substrate film including the first composite layer to a thermal aging section to thermally age the substrate film including the first composite layer.
11. The method for preparing a composite solid electrolyte according to claim 10, wherein the thermal aging is performed at 50°C to 100°C.
12. After the step (1-5), the second step is (2-1) unwinding the base film including the first composite layer using an unwinder, peeling the first composite layer from the base film, and slitting the first composite layer; and (2-2) The method for producing a composite solid electrolyte according to claim 9, further comprising a step of sintering the substrate film including the slit first composite layer to produce a ceramic ion conductor layer.
13. The method for producing a composite solid electrolyte according to claim 12, wherein the sintering is performed at 800°C to 1300°C.
14. After the (2-2) step, the third step is: (3-1) preparing a composition comprising a second polymer and a lithium salt; (3-2) coating the ceramic ion conductor layer with the composition; and (3-3) The method for producing the composite solid electrolyte according to claim 12, further comprising a step of curing the ceramic ion conductor layer coated with the composition to produce a second composite layer.
15. The method for producing a composite solid electrolyte according to claim 14, wherein the curing is thermal curing or ultraviolet curing.
16. 2. The method of claim 1, wherein a molar ratio of lithium ([Li]) to the molar concentration ([G]) of the second polymer is 0.1 to 0.
5.
17. 10. A composite solid electrolyte produced by the method of claim 1, comprising a ceramic ion conductor layer comprising a ceramic compound, a second polymer, and a lithium salt.
18. An all-solid-state battery comprising the composite solid electrolyte produced by the method of claim 1.
Citation Information
Patent Citations
High-ionic-conductivity composite solid electrolyte and preparation method thereof
CN110492170A
Polyelectrolytic element, polyelectrolytic element roll manufacturing method, and method of manufacturing polyelectrolytic element roll and battery
JP2001256826A
All-solid-state lithium-sulfur electrochemical cell and method for producing the same
JP2016524803A
Composite solid electrolyte, protection negative electrode including the same, lithium battery, and method for manufacturing composite solid electrolyte
JP2017191766A
Battery manufacturing device
JP2018160338A